Psychosocial wellbeing and physical health among Tamil schoolchildren in northern Sri Lanka. Issue 1 (December 2016) - Hamilton, Alexander; Foster, Charlie; Richards, Justin; Surenthirakumaran, Rajendra
Abstract Background Mental disorders contribute to the global disease burden and have an increased prevalence among children in emergency settings. Good physical health is crucial for mental well-being, although physical health is multifactorial and the nature of this relationship is not fully understood. Using Sri Lanka as a case study, we assessed the baseline levels of, and the association between, mental health and physical health in Tamil school children. Methods We conducted a cross sectional study of mental and physical health in 10 schools in Kilinochchi town in northern Sri Lanka. All Grade 8 children attending selected schools were eligible to participate in the study. Mental health was assessed using the Sri Lankan Index for Psychosocial Stress – Child Version. Physical health was assessed using Body Mass Index for age, height for age Z scores and the Multi-stage Fitness Test. Association between physical and mental health variables was assessed using scatterplots and correlation was assessed using Pearson's R. Results There were 461 participants included in the study. Girls significantly outperformed boys in the MH testingt (459) = 2.201, p < 0.05. Boys had significantly lower average Body Mass Index for age and height for age Z scores than girls (BMI:t (459) = −4.74, p <0.001; Height:t (459) = −3.54, p < 0.001). When compared to global averages, both sexes underperformed in the Multi-Stage Fitness Test, and had a higher prevalence of thinness and stunting. We identified no meaningful association between the selected variables. Conclusions Our results do not support the supposition that the selected elements of physical health are related to mental health in post-conflict Sri Lanka. However, we identified a considerable physical health deficit in Tamil school children.